Desain Digital Storytelling Berbasis Budaya Lokal di Pemalang sebagai Inovasi Media Pembelajaran Menulis Teks Cerpen pada Siswa SMA - Hidayat, Alfian; Setyarum, Ariesma (Pedagogical Education and Review of Linguistics, 2026)
This research is the development stage of a digital storytelling learning media based on local culture in Pemalang for innovation in learning to write short story texts in Indonesian lessons. In the research, the methods used are ADD, Analyze, Design and Development. The data obtained in this study was obtained through observation by providing questionnaires to students in grade XI (eleven) at SMA Negeri 1 Petarukan, SMK Al-Khoiriyah Petarukan and SMK Negeri 1 Petarukan. At the observation stage, it was found that the three schools were still using past learning methods such as lectures and the use of media that was limited to power point (PPT). Therefore, the researcher seeks to update the learning media so that students are motivated in learning activities. The results obtained in obtaining expert validation for digital storytelling learning media based on local culture in Pemalang obtained the following results, very feasible, namely (88%) in the media aspect, very feasible namely (94%) in the language aspect and feasible namely (77.5%) in the material aspect, with these results the digital storytelling learning media based on local culture in Pemalang is expected to be able to increase the learning motivation of students, especially in learning to write short story texts.